COMMENTS ON GUIDELINES ON DIABETES, PRE-DIABETES, AND CARDIOVASCULAR DISEASES - An. A. Alexandrov (Столичная издательская компания, 2015)
Comments on Guidelines on diabetes, pre-diabetes, and cardiovascular diseases.